INTERNALIZATION OF NATIONAL CHARACTER VALUES AT MADRASAH TSANAWIYAH PLUS AL HADI PADANGAN BOJONEGORO - Moch. Bachrurrosyady Amrullah; Ahmad Wildan Thobibi Bahja (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
Abstract: School is an educational institution that plays an active role in instilling moral and Islamic including nation values to students and plays special attention to the education of these values. The problems in this study are: (1) How is the transformation of national character values at MTs Plus al Hadi Padangan Bojonegoro (2) How is the transaction of national character values at MTs Plus al Hadi Padangan Bojonegoro (3) How is the trans-internalization of national character values at MTs Plus al Hadi Padangan Bojonegoro. The approach used in this study is a qualitative approach, because this approach is used to obtain in-depth and meaningful data about the internalization of the values of the nation's character. Therefore, this research process is expected to produce descriptive data in the form of written or oral data from people or observable behavior to provide an explanation of how the transformation, transaction and trans-internalization of the values of the nation's character at MTs Plus Al Hadi Padangan Bojonegoro. The results showed that the transformation of the values of the nation's character at MTs Plus Al Hadi Padangan Bojonegoro used various methods, namely through the lecture method, advice and motivation, the affirmation icon method, the story method, and various extracurricular activities as well as other agendas containing the values of the nation's character. The transaction of national character values went quite well, the teacher gave an example to students about positive character and students responded well even though there were a few students who did not respond well. Trans-internalization of national character values at MTs Plus Al Hadi Padangan Bojonegoro went well because teachers at MTs Plus Al Hadi showed their personality to students and they always did self-introspection.Keyword: Internalization, National Character Values